2020
DOI: 10.25115/eea.v30i2.3542
|View full text |Cite
|
Sign up to set email alerts
|

Who Bets on Sports? Characteristics of Sports Bettors and the Consequences of Expanding Sports Betting Opportunities

Abstract: Currently, several proposed changes in sports betting laws are being debated in the United States and the European Union. This article examines the characteristics of sports bettors in three countries, Canada, Spain, and the United Kingdom, to determine who bets on sports in environments where this activity is both legal and popular. Unconditional and conditional analyses find that annual participation rates in sport betting are low, and that sport bettors tend to be young males with relatively high incomes. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…These factors may help to explain the age-related results presented here as the Spanish sample may have a later access to play, resulting in younger ages being partially underrepresented. In the past, country-related differences regarding younger ages accessing to sports betting has been reported (Humphreys & Perez, 2012). We additionally found that older age was a predictor of gambling-related debts, reinforcing the idea that in our sample older ages are consistent with more severe sports betting trajectories.…”
Section: Discussionsupporting
confidence: 88%
“…These factors may help to explain the age-related results presented here as the Spanish sample may have a later access to play, resulting in younger ages being partially underrepresented. In the past, country-related differences regarding younger ages accessing to sports betting has been reported (Humphreys & Perez, 2012). We additionally found that older age was a predictor of gambling-related debts, reinforcing the idea that in our sample older ages are consistent with more severe sports betting trajectories.…”
Section: Discussionsupporting
confidence: 88%
“…The regression results also indicated that impulse betting both before and after match commencement was more frequent among younger sports bettors. Young men in particular predominate among sports bettors ( Humphreys & Pérez, 2012 ; Wood & Williams, 2011 ) and are the target market for sports-betting advertising, including promotions for incentivized bets during play. Sproston et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries globally permit unrestricted sports betting and often encourage the act, often in partnership with national regulatory bodies. Humphreys and Perez [13] noted that governments generally overlook the negative impacts of sports betting, in favour of the revenues it generates through the regulation and taxation of this activity.…”
Section: Introductionmentioning
confidence: 99%